International scholars in academic semi-peripheries : – a sign of research excellence or a remedy for staff shortages? (Comparative & International Education Series, 2021)
In this paper, we hypothesize that foreign-born employees in Poland are often not a sign of internationalization or research excellence, but rather a remedy for staff shortages experienced by smaller and less prestigious universities. The study is based on an analysis of register data on employees of Polish universities. This paper is a follow-up to our previous study on the role of international scholars in another European semi-periphery – Slovakia. We identify factors related to a higher share of foreign-born scholars and discuss these in the context of our qualitative research based on semi-structured interviews. The study has demonstrated that academic migrants to Poland are employed more often by universities with a lower academic prestige and located outside the national academic centers. Thus, academic migration patterns in Central Europe are different from these revealed in the studies focused on North America and Western Europe.